2013
DOI: 10.1007/s10437-013-9128-1
|View full text |Cite
|
Sign up to set email alerts
|

The History of African Village Chickens: an Archaeological and Molecular Perspective

Abstract: The history of the introduction and dispersal of village chickens across the African continent is a subject of intense debate and speculation among scholars. Here, we synthesize and summarise the current scientific genetic and nongenetic knowledge in relation to the history of the species on the continent. Sociocultural, linguistic, archaeological and historic data all suggest a complex history for the species in Africa, characterized by multiple maritime and/or terrestrial introductions over time and several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
59
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 41 publications
1
59
0
Order By: Relevance
“…Thus, they travel well with people versed in their needs and behavior. In this issue, Mwacharo et al (2013) suggest that multiple lineages of South Asian and Southeast Asian domestic chickenincluding two relatively rare ones-followed several different paths of entry into Africa, which in turn may reflect divergent, sometimes temporally successive, systems of commercial contact.…”
Section: Chickenmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, they travel well with people versed in their needs and behavior. In this issue, Mwacharo et al (2013) suggest that multiple lineages of South Asian and Southeast Asian domestic chickenincluding two relatively rare ones-followed several different paths of entry into Africa, which in turn may reflect divergent, sometimes temporally successive, systems of commercial contact.…”
Section: Chickenmentioning
confidence: 99%
“…As Mwacharo et al (2013) note, this chicken haplogroup is most diverse in Indonesia, the original home of seafaring migrants who settled Madagascar in the mid-first millennium AD. One would expect that these migrants carried chickens with them, as well as other typically Southeast Asian crops such as rice and banana, yet the authors report the Malagasy word for chicken is of Bantu origin (Blench 2006).…”
Section: Chickenmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays RJFs are hybridizing with native chickens to produce meat for human consumption. Therefore, it is necessary to estimate genetic interrelationship among RJFs existed in Asiatic countries.The nucleotide sequence of mtDNA D-loop region is an important tool to find out the origin and genetic diversity of domestic animals (Beja-Pereira et al, 2006;Amills et al, 2008), and to investigate the origin and phylogeny of fowls as a genetic information of the ancestry that descended from female fowls as maternal inheritance.A number of studies have investigated the origin and dispersion of domestic chickens (Crawford, 1990;Mwacharo et al, 2013). Akishinonomiya et al (1996) reported that the present domestic chickens have originated from Gallus gallus gallus in Thailand and adjacent regions.…”
mentioning
confidence: 99%
“…A number of studies have investigated the origin and dispersion of domestic chickens (Crawford, 1990;Mwacharo et al, 2013). Akishinonomiya et al (1996) reported that the present domestic chickens have originated from Gallus gallus gallus in Thailand and adjacent regions.…”
mentioning
confidence: 99%